Determination of chromium by GFAAS in slurries of fish feces to estimate the apparent digestibility of nutrients in feed used in pisciculture - Silva, F. A.; Padilha, CCF; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP]; Padilha, Pedro de Magalhães [UNESP] (Elsevier B.V., 2006)
This paper presents a simple, fast and sensitive method to determine chromic oxide (used as a biological marker of fish feed) in samples of fish feces by GFAAS through the direct introduction of slurries of the samples into the spectrometer's graphite tube. The standard samples of feces and of fish feed containing 0.10-1.00 mg kg(-1) of Cr2O3 were pre-frozen for I min in liquid nitrogen and then ground a cryogenic mill for 2 min, which reduced the samples' grain size to less than 60 mu m. The standard slurries were prepared by mixing 20 mg of standard samples of fish feed or feces with I mL of a solution containing 0.05% (v/v) of Triton X-100 and 0.50% (v/v) of suprapure HNO3 directly in the spectrometer's automatic sampling glass. The final concentrations of Cr2O3 present in the standard slurries were 2, 4, 8, 16 and 20 mu g L-1. After sonicating the mixture for 20s, 10 mu L of standard slurries were injected into the graphite tube, whose internal wall was lined with a metallic palladium film that acted as a permanent chemical modifier. The limits of detection (LOD) and quantification (LOQ) calculated for 20 readings of the blank of the standard slurries (2%, m/v of feces or feed devoid of minerals) were 0.81 and 2.70 mu g L-1 of Cr2O3 for the standard feces slurries, 0.84 and 2.83 mu g L-1 of Cr2O3 for the standard feed slurries. The proposed method was applied in studies of nutrient digestibility of different fish feeds and its results proved compatible with the results obtained from samples pre-mineralized by acid digestion. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: slurries samples; GFAAS; metallic palladium; chromic oxide